Consumers' perceptions, attitudes and willingness to pay towards food products with "No Added MSG" labeling - Radam, Alias; Yacob, Mohd Rusli; Than, Siew Bee; Selamat, Jinap (Canadian Center of Science and Education, 2010)
This research was carried out in order to determine consumers’ perceptions, attitudes and willingness-to-pay (WTP) towards food products with “No Added MSG” labeling. A total of 200 respondents within the area of Klang Valley were interviewed using a close-ended questionnaire. The Contingent Valuation Method (CVM) was used to determine the consumers’ WTP for the consumption of safer beef. A logit model was used to estimate the premium that consumers are willing to pay for food products with “No Added MSG” labeling. The results pointed out that majority of the consumers know and have read about or heard of Monosodium Glutamate (MSG) and illnesses caused by MSG, but only a small portion of them have experienced these illnesses before. Not all of the consumers have high awareness towards illnesses caused by MSG due to lack of information. However, their perceptions and attitudes towards food products with “No added MSG” labeling were found to be generally positive. Besides, the CV method which was used to determine and estimate consumers’ WTP towards the food products mentioned by using logit model showed that the most important and significant actors that influenced a consumers’ WTP are gender (female), household size, household income, family member with children below the age of 12, price levels and education level (university). Results also revealed that respondents were willing to pay a premium of about RM 0.43 for food products with “No added MSG” labeling. Based on the study, it was found that the demand and consumption of “No Added MSG” is still high and increasing. This current trend will certainly have effects on the present market. Hence, to ensure a better development of these products, there is a need to formulate proper standards, policies and promotion programmes for these products more efforts in research and development (R&D) are needed to improve the production technologies and food safety systems for these “No Added MSG” food products.